2003
DOI: 10.1002/ar.a.10030
|View full text |Cite
|
Sign up to set email alerts
|

Porcine intrinsic cardiac ganglia

Abstract: The gross, light, and electron microscopic anatomies of the porcine intrinsic cardiac nervous system were investigated in 26 pigs to facilitate functional studies in this model. Gross anatomy: Numerous ganglia and interconnecting nerves (ganglionated plexuses) were found to be concentrated in epicardial fat in five atrial and six ventricular regions. The five atrial ganglionated plexuses identified were (1) the ventral right atrial, (2) the right vena cava-right atrial, (3) the dorsal atrial, (4) the interatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 34 publications
2
62
1
3
Order By: Relevance
“…21 Numerous studies have observed multiple major and small GPs in the atria of mammalian hearts. 19,[22][23][24] These GPs modulate the interaction and balance between the extrinsic and intrinsic autonomic nervous system and contain efferent cholinergic and adrenergic neurons which influence the atrial myocardium, 25 in terms of action potential duration, AERP, and conduction velocity. In many animal studies, autonomic denervation exhibited short-term efficacy.…”
Section: Changes In the Electrophysiological Characteristics In The Tmentioning
confidence: 99%
“…21 Numerous studies have observed multiple major and small GPs in the atria of mammalian hearts. 19,[22][23][24] These GPs modulate the interaction and balance between the extrinsic and intrinsic autonomic nervous system and contain efferent cholinergic and adrenergic neurons which influence the atrial myocardium, 25 in terms of action potential duration, AERP, and conduction velocity. In many animal studies, autonomic denervation exhibited short-term efficacy.…”
Section: Changes In the Electrophysiological Characteristics In The Tmentioning
confidence: 99%
“…From a number of neuroanatomically investigated mammalian species it is known that cardiac ganglia are mainly distributed on certain atrial regions around the sinuatrial node, at the roots of the vena cava and pulmonary veins, above and within the interatrial septum, in the proximity of atrioventricular node and, even in the auricular appendages (King and Coakley 1958;Navaratnam 1965;BojsenMoller and Tranum-Jensen 1971;Baptista and Kirby 1997;Pauza et al 1999Pauza et al , 2000Pauza et al , 2002aBatulevicius et al 2003Batulevicius et al , 2004Batulevicius et al , 2005. Structural organization of the intracardiac nerve plexus of the human and many animal models has been previously described using histological, histochemical and immunohistochemical methods (Bojsen-Moller and Tranum-Jensen 1971;Khabarova 1975;Stropus and Vaicekauskas 1978;Yuan et al 1994;Marron et al 1995;Singh et al 1996;Armour et al 1997;Pauza et al 1999Pauza et al , 2000Pauza et al , 2002aBatulevicius et al 2003Batulevicius et al , 2004Batulevicius et al , 2005Arora et al 2003;Jurgaitiene et al 2004;etc.). Histochemical study of the total adult human hearts, including hearts of children, infants, neonates and three fetuses of the late gestation, performed by Pauza et al (2000), have demonstrated the morphological pattern of the human epicardiac neural ganglionated plexus that contains 836 ± 76 ganglia.…”
Section: Introductionmentioning
confidence: 91%
“…However, a direct microcirculatory interconnection between the two has not been established so far. 23,24 Nonetheless, owing to its unique anatomic juxtaposition, numerous plausible physiological roles have been offered to epicardial fat including, but not limited to, that (1) it serves as the anatomic site for the cardiac nervous system, 25 (2) it serves to cushion the coronary arteries against pulse wave torsion, 14 (3) it serves as a heating blanket to protect the myocardium during hypothermia, 26,27 (4) it is an immunological tissue that serves to protect the myocardium and coronaries against pathogens and inflammatory activators 28 and (5) it serves to maintain fatty acid homeostasis in the coronary microcirculation. 5 In a seminal study looking at the anatomy, histology and biochemical properties of epicardial fat across a spectrum of species, epicardial fat was reported to exhibit a higher capacity for breakdown, synthesis and release of fatty acids relative to other intra-abdominal fat depots in guinea pigs.…”
Section: Physiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%